Diversity and abundance of odonates (dragonflies and damselflies) and lepidopteran (butterflies) fauna of Kalyani Lake Park, Nadia district, West Bengal, India - Dolai , Sayak; Md Abu Imran Mallick, Md Abu Imran Mallick; Ghorai , Narayan (Academia Journal of Biology, 2025)
Butterflies, dragonflies and damselflies are indeed important for ecosystem productivity, playing roles in pollination and insect control, contributing to a balanced and thriving ecosystem. Their presence showcases the health and abundance of the ecosystem. Biodiversity protection and conservation are indeed essential aspects of both national and international agendas, as they contribute significantly to the sustainable development of regions and countries. Biodiversity ensures the health and stability of ecosystems, provides ecosystem services crucial for human survival and well-being, and supports various industries such as agriculture, fisheries, and tourism. Lepidoptera and Odonata assemblage along with Kalyani Lake Park of Nadia district in West Bengal has been investigated. The study on dragonflies, damselflies and butterfly species were conducted from August 2021 to September 2023. A modified “Pollard Walk” method was used to record species and abundance. In this survey, 25 species of dragonflies, 10 species of damselflies and 75 species of Butterflies were recorded. Among the odonate species, Libelluidae and Coenagrionidae were the dominant families with the maximum number of species being 23 and 08, respectively. In the case of butterflies, Nymphalidae was the dominant family with 27 species while others have fewer representatives. Relative abundance and diversity indices were calculated for all species groups. However, in the case of the urban forest area, the observed high anthropogenic disturbances create significant biotic pressure on the Kalyani Lake Park. Given the significance of understanding the insect diversity in this study area, a detailed list of recorded Odonata and Lepidoptera from the study would provide valuable insights into the specific species present, their distribution, and their potential interactions with the environment.